The Free Energy of a Quantum Sherrington–Kirkpatrick Spin-Glass Model for Weak Disorder - Leschke, Hajo; Rothlauf, Sebastian; Ruder, Rainer; Spitzer, Wolfgang (Journal of Statistical Physics, 2021)
We extend two rigorous results of Aizenman, Lebowitz, and Ruelle in their pioneering paper of 1987 on the Sherrington–Kirkpatrick spin-glass model without external magnetic field to the quantum case with a “transverse field” of strength b. More precisely, if the Gaussian disorder is weak in the sense that its standard deviation v> 0 is smaller than the temperature 1 / β, then the (random) free energy almost surely equals the annealed free energy in the macroscopic limit and there is no spin-glass phase for any b/ v≥ 0. The macroscopic annealed free energy turns out to be non-trivial and given, for any βv> 0 , by the global minimum of a certain functional of square-integrable functions on the unit square according to a Varadhan large-deviation principle. For βv< 1 we determine this minimum up to the order (βv) 4 with the Taylor coefficients explicitly given as functions of βb and with a remainder not exceeding (βv) 6/ 16. As a by-product we prove that the so-called static approximation to the minimization problem yields the wrong βb-dependence even to lowest order. Our main tool for dealing with the non-commutativity of the spin-operator components is a probabilistic representation of the Boltzmann–Gibbs operator by a Feynman–Kac (path-integral) formula based on an independent collection of Poisson processes in the positive half-line with common rate βb. Its essence dates back to Kac in 1956, but the formula was published only in 1989 by Gaveau and Schulman.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Annealed free energy; Feynman–Kac formula; Quantum spin-glas model; Varadhan large-deviation principle